International trade, growth and development - Bardhan, Pranab (Oxford, 2003)
This collection of essays draws from over thirty years of work by noted economist Pranab Bardhan to address the interrelated themes of international trade, growth, and rural development. Covering a wide range of important issues within the field, these essays describe theoretical and empirical perspectives on economic agents both at the micro and macro levels of the economy in development. Additionally, introductions to each of the book's three sections place the articles in perspective and relate them to current research. The essays analyze such issues as: various constraints faced by poor countries trading with rich countries, the implications of vintage capital models for trade and growth, and the nature of contracts in rural markets of poor countries. The intensive empirical studies concerning this last issue (using both large datasets and field surveys) work to provide a solid foundation for a more authentic theory of rural development. This collection will make available some widely cited articles that are not always easy to find, in addition to serving as an overview of Bardhan's significant contribution to these areas of study.
Keywords: Trade